2006
DOI: 10.1103/physrevb.74.214520
|View full text |Cite
|
Sign up to set email alerts
|

Flux-flow-induced giant magnetoresistance in all-amorphous superconductor-ferromagnet hybrids

Abstract: We present magnetoresistance measurements on all-amorphous ferromagnet (F) / superconductor (S) heterostructures. The F/S/F trilayers show large magnetoresistance peaks in a small field range around the coercive field of the F layers, at temperatures within and below the superconducting transition. This is interpreted as flux flow of weakly pinned vortices induced by the stray field of Bloch magnetic domains in the F layers. Bilayers show much smaller effects, implying that the Bloch walls of the F-layers in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 22 publications
8
32
0
Order By: Relevance
“…Based on this idea experiments, performed by Steiner et al [10] on Fe/Nb and Co/Nb bilayers, found a reduction of T C ≈ 0.5% as a function of magnetic state of the ferromagnet. Additionally Bell et al [11] have found a double peak structure in magnetoresistance measurements of MoGe/GdNi bilayered structures as a function of the magnetic state of the ferromagnet attributed to vortex formation and flux flow.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this idea experiments, performed by Steiner et al [10] on Fe/Nb and Co/Nb bilayers, found a reduction of T C ≈ 0.5% as a function of magnetic state of the ferromagnet. Additionally Bell et al [11] have found a double peak structure in magnetoresistance measurements of MoGe/GdNi bilayered structures as a function of the magnetic state of the ferromagnet attributed to vortex formation and flux flow.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is that the thermodynamic and transport properties of FSF trilayers are found to depend strongly on the relative orientation of the magnetization in the two F layers. 5,6,7,8 This rather well-understood 9,10,11,12 fact makes these structures candidates as spin valves.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting effects that arise from the interplay between these orderings have potential technological applications in fields such as spintronics [3]. For example, the relative orientation of the magnetizations in the F layers in FSF trilayers can have a strong influence on the conductivity [4,5,6,7,8], making them good spin valve candidates. Such trilayers were first proposed [9] for insulating F layers and later for metallic [10,11] ones.…”
mentioning
confidence: 99%